Scalable Manufacturing of Mechanical Robust Bioinspired Ceramic–Resin Composites with Locally Tunable Heterogeneous Structures. Issue 14 (26th February 2023) - Zhang, Zhen‐Bang; Gao, Huai‐Ling; Wen, Shao‐Meng; Pang, Jun; Zhang, Si‐Chao; Cui, Chen; Wang, Ze‐Yu; Yu, Shu‐Hong
Abstract: Lightweight structural materials with a unique combination of high stiffness, strength, toughness, and hardness, are highly desired yet challenging to be artificially fabricated. Biological structural materials, on the other hand, ingeniously integrate multiple mutually exclusive mechanical properties together relying on their hierarchically heterogeneous structures bonded with gradient interfaces. Here, a scalable bottom‐up approach combining continuous nanofiber‐assisted evaporation‐induced self‐assembly with laminating, pressure‐less sintering and resin infiltration is reported to fabricate bioinspired heterogeneous ceramic–resin composites with locally tunable microstructure to fulfill specific properties. A gradient interlayer is introduced to provide a gradual transition between adjacent heterogeneous layers, effectively alleviating their property mismatch. The optimized heterogeneous nacre‐like composite, as a demonstration, exhibits an attractive combination of low density (≈2.8 g cm −3 ), high strength (≈292 MPa), toughness (≈6.4 MPa m 1/2 ), surface hardness (≈1144 kgf mm −2 ) and impact‐resistance, surpassing the overall performance of engineering alumina. This material‐independent approach paves the way for designing advanced bioinspired heterogeneous materials for diverse structural and functional applications. Abstract : By developing a simple bottom‐up assembly approach, nacre‐like ceramic–resin composites with tunable heterogeneous architectures are scalably manufactured. The composites are designed with a strong and tough nacre‐like main body, and a stiff and hard surface layer bonded by a gradient interlayer to alleviate property mismatch. This structural design achieves an impressive combination of low density and multiple desired mechanical properties.